Pengaruh Religiusitas dan Literasi Keuangan Syariah terhadap Keputusan Pengusaha Mikro Melakukan Pembiayaan Al Qardh di Bankziska Ponorogo - Rahayu, Dwi; Amri, Muhtadin (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2023)
Al-Qardh is a Tabbaru contract which is generally carried out by Islamic financial institutions with the principle of virtue besides that it is carried out by Bankziska Ponorogo in helping to alleviate micro-entrepreneurs from the trap of loan sharks. In Ponorogo the level of religiosity is quite good with the number of Islamic boarding schools and faith-based schools, but in fact there are still many people in Ponorogo who are currently entangled in loans with very high interest rates (thithil banks), especially among MSMEs that are classified as micro. Based on these problems, this study aims to examine and analyze the influence of the theory of religiosity and Islamic financial literacy on the decision of micro-entrepreneurs to finance Al-Qardh at Bankziska Ponorogo. The method used in this study is a quantitative method with questionnaire media through questionnaires and google forms to collect data. The sample of this study was 100 respondents who were MSMEs micro-entrepreneurs Bankziska Ponorogo with purposive sampling techniques. Data analysis techniques with the help of Smart PLS software that uses validity, reliability, descriptive analysis, instruments and hypotheses.. The results of this study show that religiosity and Islamic financial literacy have a significant effect on Al-Qardh's financing decisions both partially and simultaneously. Thus, factors of religiosity and Islamic financial literacy can determine the decision of micro-entrepreneurs to finance Al-Qardh at Bankzsika Ponorogo. Al – Qardh merupakan akad Tabbaru’ yang pada umumnya dilakukan oleh lembaga keuangan syariah dengan prinsip kebajikan selain itu dilakukan oleh Bankziska Ponorogo dalam membantu mengentaskan pengusaha mikro dari jeratan rentenir. Di Ponorogo tingkat religiusitas terbilang cukup baik dengan ditandai banyaknya pesantren dan sekolah yang berbasis keagamaan, namun pada kenyataannya masyarakat di Ponorogo saat ini masih banyak sekali yang terjerat pinjaman dengan nilai bunga yang sangat tinggi (bank thithil), khususnya dikalangan UMKM yang tergolong mikro. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk menguji dan menganalisis pengaruh teori religiusitas dan literasi keuangan syariah terhadap keputusan pengusaha mikro melakukan pembiayaan Al – Qardh di Bankziska Ponorogo. Metode yang digunakan dalam penelitian ini ialah metode kuantitatif dengan media kuisioner melalui angket dan google form untuk mengumpulkan data. Sampel penelitian ini sebanyak 100 responden yang merupakan UMKM pengusaha mikro Bankziska Ponorogo dengan teknik purposive sampling. Teknik analisis data dengan bantuan software Smart PLS yang menggunakan uji validitas, reliabilitas, analisis deskriptif, intrumen dan hipotesis. Hasil penelitian ini menunjukkan bahwa religiusitas dan literasi keuangan syariah berpengaruh signifikan terhadap keputusan pembiayaan Al – Qardh baik secara parsial maupun simultan. Dengan demikian, faktor religiusitas dan literasi keuangan syariah dapat menentukan keputusan pengusaha mikro untuk pembiayaan Al–Qardh di Bankzsika Ponorogo.